Subcircuit-specific neuromodulation in the prefrontal cortex - Dembrow, Nikolai; Johnston, Daniel (Frontiers in Neural Circuits, 2014)
During goal-directed behavior, the prefrontal cortex (PFC) exerts top-down control over numerous cortical and subcortical regions. PFC dysfunction has been linked to many disorders that involve deficits in cognitive performance, attention, motivation, and/or impulse control. A common theme among these disorders is that neuromodulation of the PFC is disrupted. Anatomically, the PFC is reciprocally connected with virtually all neuromodulatory centers. Recent studies of PFC neurons, both in vivo and ex vivo, have found that subpopulations of prefrontal projection neurons can be segregated into distinct subcircuits based on their long- range projection targets, and that these subpopulations differ in their connectivity, intrinsic properties, and responses to neuromodulators. In this review we outline the evidence for subcircuit-specific neuromodulation in the PFC, and describe some of the functional consequences of selective neuromodulation on behavioral states during goal-directed behavior.